16. Myrrhido-Valerianetum pyrenaicae versus Chaerophyllo hirsuti-Valerianetum pyrenaicae - Izco, Jesús (Lazaroa, 2014)
Myrrhido-Valerianetum pyrenaicae versus Chaerophyllo hirsuti-Valerianetum pyrenaicae